Warburg effect and lactylation in cancer: mechanisms for chemoresistance - Wenjie Zhang; Min Xia; Jiahui Li; Gaohua Liu; Yan Sun; Xisha Chen; Jing Zhong (Molecular Medicine)
Abstract In the clinical management of cancers, the emergence of chemoresistance represents a profound and imperative “pain point” that requires immediate attention. Understanding the mechanisms of chemoresistance is essential for developing effective therapeutic strategies. Importantly, existing studies have demonstrated that glucose metabolic reprogramming, commonly referred to as the Warburg effect or aerobic glycolysis, is a major contributor to chemoresistance. Additionally, lactate, a byproduct of aerobic glycolysis, functions as a signaling molecule that supports lysine lactylation modification of proteins, which also plays a critical role in chemoresistance. However, it is insufficient to discuss the role of glycolysis or lactylation in chemoresistance from a single perspective. The intricate relationship between aerobic glycolysis and lactylation plays a crucial role in promoting chemoresistance. Thus, a thorough elucidation of the mechanisms underlying chemoresistance mediated by aerobic glycolysis and lactylation is essential. This review provides a comprehensive overview of these mechanisms and further outlines that glycolysis and lactylation exert synergistic effects, promoting the development of chemoresistance and creating a positive feedback loop that continues to mediate this resistance. The close link between aerobic glycolysis and lactylation suggests that the application of glycolysis-related drugs or inhibitors in cancer therapy may represent a promising anticancer strategy. Furthermore, the targeted application of lactylation, either alone or in combination with other treatments, may offer new therapeutic avenues for overcoming chemoresistance.